Evaluasi Nilai Volume Produksi Overburden di PT Ansaf Inti Resources Site Berambai Bulan September 2022 - Muhammad Havit Pratama; Dawamul Arifin; Radik Khairil Insanu; Nia Kurniadin (Journal of Geomatics Engineering, Technology, and Science, 2023)
Ansaf Inti Resources is located in Kec. Kutai Kartanegara, East Kalimantan. The coal mining process is preceded by excavation of overburden or activities carried out prior to coal getting to meet its production target, in determining the volume of overburden stripping in the Alam 4 pit survey activities are carried out and the determination of the rate of conveyance. In survey activities carried out by measuring the coordinates of X/easting, Y/northing and Z/elevation. The purpose of conducting research on, "Knowing the Value of Mine Production Volume based on Overburden Material Stripping survey data, truck count data Using Surpac Software" is to know the measurement of overburden progress survey in the mining area, know the calculation of overburden progress survey volume and find out the results of comparison of progress survey volume with calculations the number of trucks carrying overburden. The methodology used in this study consisted of the research preparation stage, the data collection stage, namely secondary data obtained indirectly from the survey team in the field. The results of measurements and calculations regarding the progress survey conducted in September 2022 obtained the overburden volume value in the first week of 76,289.77 BCM/m3, in the second week the overburden volume value was obtained 55,826.43 BCM/m3, in the third week the results were obtained the result of the overburden volume value is 44,179.01 BCM/m3, in the fourth week the result of the overburden volume value is 60,290.74 BCM/m3.